2012
DOI: 10.3164/jcbn.11-33
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of dimethylargininedimethylaminohydrolase/asymmetric dimethylarginine pathway in rat type II diabetic nephropathy

Abstract: An impaired generation of nitric oxide has been associated with diabetic renal disease. In order to elucidate the underlying molecular mechanisms into how nitric oxide synthesis is impaired in diabetic renal disease, we examined changes in activities and expressions of some renal enzymes involved in nitric oxide production during the development of diabetic nephropathy in type II diabetic Otsuka Long-Evans Tokushima Fatty rats. Ten-week old Otsuka Long-Evans Tokushima Fatty (n = 40) and control Long-Evans Toku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Treatment against fibrosis with the early utilization of angiotensin-converting enzyme inhibitors may be a potential diabetic strategy (11). Dimethylarginine dimethylaminohydrolase (DDAH) dysregulation has been found to exert notable effect during the progression of diabetic nephropathy through elevating asymmetric dimethylarginine levels (12). Therefore, the present study investigated the role of DDAH2 under experimental diabetic conditions to test the hypothesis that DDAH2 dysregulation is involved in the progression of fibrosis in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment against fibrosis with the early utilization of angiotensin-converting enzyme inhibitors may be a potential diabetic strategy (11). Dimethylarginine dimethylaminohydrolase (DDAH) dysregulation has been found to exert notable effect during the progression of diabetic nephropathy through elevating asymmetric dimethylarginine levels (12). Therefore, the present study investigated the role of DDAH2 under experimental diabetic conditions to test the hypothesis that DDAH2 dysregulation is involved in the progression of fibrosis in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…NO is identified as an important regulator of renal function and morphology ( 28 ). Asymmetric dimethylarginine can be metabolized to citrulline, which potentially prevents the inhibition of endothelial nitric oxide synthase by asymmetric dimethylarginine ( 29 ). The elevation level of citrulline in DN patients may be related to dysregulation of the renal NO-producing system.…”
Section: Discussionmentioning
confidence: 99%
“…By impairing the production of nitric oxide, ADMA contributes to the development of vascular malfunctioning 16,17 . Many studies have reported that elevated ADMA concentration in the circulation is a potential biomarker for the prediction of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%